2006
DOI: 10.3346/jkms.2006.21.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-Tocopherol on Cadmium-Induced Toxicity in Rat Testis and Spermatogenesis

Abstract: Cadmium is known to exert toxic effects on multiple organs, including the testes. To determine if α-Tocopherol, an antioxidant, could protect testicular tissues and spermatogenesis from the toxic effects of cadmium, six-week old male Sprague-Dawley rats were randomized to receive cadmium at doses of 0 (control), 1, 2, 4 or 8 mg/kg by the intraperitoneal route (Group A) or α-tocopherol for 5 days before being challenged with cadmium (Group B) in an identical dose-dependent manner. When both groups received cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
65
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 35 publications
16
65
0
3
Order By: Relevance
“…Several studies have reported that antioxidants and vitamins A, B, C, and E can protect sperm's DNA from free radicals, and also, increase barrier stability of blood testis (Jedlinska- (Khaki et al, 2009). Antioxidants protect DNA and other important molecules from oxidation and damage, improve sperm quality, and consequently, increase fertility rate in men (Yang et al, 2006). Therefore, the role of nutritional and biochemical factors in reproduction and sub-fertility treatment is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that antioxidants and vitamins A, B, C, and E can protect sperm's DNA from free radicals, and also, increase barrier stability of blood testis (Jedlinska- (Khaki et al, 2009). Antioxidants protect DNA and other important molecules from oxidation and damage, improve sperm quality, and consequently, increase fertility rate in men (Yang et al, 2006). Therefore, the role of nutritional and biochemical factors in reproduction and sub-fertility treatment is very important.…”
Section: Introductionmentioning
confidence: 99%
“…A slight adjustment in the intraperitoneal dose of cadmium results in severe changes in testicular morphology. Predes, Diamante, and Dolder (2010) and Yang et al (2006) showed that a single cadmium ip injection of 1.0 mg/kg BW (body weight) did not result in any marked morphological change in rodent testis 56 days following the exposure to the metal. On the other hand, ip doses ranging between 1.15 and 1.2 mg/kg BW are reported to cause drastic alterations in the testis, including seminiferous epithelium depletion, vasoconstriction, and Leydig cell numerical reduction (Leite et al 2011;Predes, Diamante, and Dolder 2010) Based upon the data presented, the current study investigates whether P. cupana supplementation, after cadmium exposure, has the potential to reduce the testicular impairments normally observed in Wistar rats exposed to this metal.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ginger can improve sperm quality and consequently increase fertility rate in men [54,55]. Similar results were reported by Mares and Najam (2012) [56] who mentioned that, there was a significant (p<0.01) increase in sperm count (16.2%), sperm motility (47.3%), sperm viability and normal sperm morphology (40.7%), ejaculate volume (36.1%) and significant increase was observed for serum FSH, LH and testosterone levels of infertile men after treatment with ginger as compared with that before treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants protect DNA and other important molecules from oxidation and damage and can improve sperm quality and consequently increase fertility rate in men [17,18].…”
Section: Introductionmentioning
confidence: 99%